The effect of learning an individualized song on autobiographical memory recall in individuals with Alzheimer's disease: A pilot study. Issue 7 (9th August 2019) - Fraile, Elodie; Bernon, Daisy; Rouch, Isabelle; Pongan, Elodie; Tillmann, Barbara; Lévêque, Yohana
ABSTRACT: Numerous neuropsychological studies have investigated the effect of music on patients with Alzheimer's disease. Findings suggest that music can improve behavioral symptoms, but its potential effects on cognitive abilities of patients still require more investigation. In this 2 × 2 crossover study, we measured the impact of learning an individualized song on autobiographical memory recall and other cognitive abilities in 12 patients with mild to moderate Alzheimer's disease. For each patient, one favorite song of the patient and one autobiographical memory with positive valence were associated to create a new personalized song. This song was taught to the patient by a speech and language therapy student throughout 10 sessions. This training period and a non-training period were proposed in a counterbalanced order between participants. We tested participants' autobiographical recall and general cognitive abilities at three time points: at the start of the experiment, at crossover, and at the end of the experiment. After excluding one outlier, results showed a significant improvement in the retrieval of the autobiographical memory and in general cognitive abilities after song training compared to the non-training period. Overall, our findings suggest that the use of personalized songs may be a useful and motivating tool for addressing the decline of autobiographical memory and of cognitive functions in general in persons with Alzheimer's disease.